Publics and their health : historical problems and perspectives - Mold, Alex (Social histories of medicine., 2023)
Why are some groups and individuals seen as problems for public health? How does this change over time and place? Through a series of case-studies, this collection explores the making of 'problem publics' and their relationship with public health authorities.